Rethinking Emotional Stability: Uncovering the Role of Suppressed Emotions and Social Desirability Bias Among Women Educators - Shalini Das; Shubha Chandra (CV. Doki Course and Training, 2026)
Emotional stability is considered as a protective personality trait when looked up in psychological literatures that are associated with lowering stress and enhancing well-being (Steel et al., 2008; Kroencke, Geukes, & Denissen, 2020). However, a pilot study of women educators revealed an unexpected positive correlation between emotional stability and perceived stress (Das, 2025). This paradox is confounding and suggests gaps in assumptions that have been made about personality traits and their expression and measurement within a given culture and professional framework. One possibility focuses on emotional suppression and social desirability, which is the phenomenon in which people report higher emotional stability in order to conform to social expectations while undergoing heightened psychological stress (Gross & John, 2003; Paulhus, 2002). This is especially the case for women professionals in collectivist cultures, who are admired for their calmness and self-restraint (Matsumoto, Yoo, & Nakagawa, 2008) a prominent personality aspect of a respectable women under the Indian societal lookout. The study illustrates the need to refine personality–stress models to incorporate gendered, culturally discriminated coping strategies that subvert conventional trait–outcome relationships. These findings, in particular, urge us to exercise methodological caution and propose context-sensitive, mixed-method frameworks in stress and personality research.